1997
DOI: 10.1161/01.cir.96.8.2649
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Chronic Garlic Intake on Elastic Properties of Aorta in the Elderly

Abstract: Chronic garlic powder intake attenuated age-related increases in aortic stiffness. These data strongly support the hypothesis that garlic intake had a protective effect on the elastic properties of the aorta related to aging in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 36 publications
0
51
2
1
Order By: Relevance
“…Previous studies reported that elastic properties of the aorta decrease with age. 23,24 Although the exact mechanisms of progression in patients with IMH remains unclear, decreased distensibility of descending aorta may play an important role in the disease process in patients with IMH. 12,25 One limitation of this study was relatively small sample number for multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that elastic properties of the aorta decrease with age. 23,24 Although the exact mechanisms of progression in patients with IMH remains unclear, decreased distensibility of descending aorta may play an important role in the disease process in patients with IMH. 12,25 One limitation of this study was relatively small sample number for multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…34 PWV (m  s À1 ) was calculated as the ratio between the distance travelled by the pulse wave and pulse transmission time. 34 Augmentation index was calculated from pulse waves of the common carotid artery that were recorded by applanation tonometry.…”
Section: Anthropometric and Haemodynamic Parametersmentioning
confidence: 99%
“…34 PWV (m  s À1 ) was calculated as the ratio between the distance travelled by the pulse wave and pulse transmission time. 34 Augmentation index was calculated from pulse waves of the common carotid artery that were recorded by applanation tonometry. 1,10 Data were collected directly into a portable computer; integral software was used to generate an averaged peripheral waveform (SphygmoCor, PWV Medical, Sydney, Australia).…”
Section: Anthropometric and Haemodynamic Parametersmentioning
confidence: 99%
“…PWV (m/s) was calculated as the ratio between the distance travelled by the pulse wave and pulse transmission time. 19 Pulse wave analysis was performed in 72 subjects (CC, n ¼ 30; TC&TT, n ¼ 42), as previously described by our laboratory. 16,20 Central haemodynamics were calculated from radial pulse waves that were recorded by applanation tonometry.…”
Section: Anthropometric and Haemodynamic Parametersmentioning
confidence: 99%